2020
DOI: 10.1038/s41598-020-78359-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a human primary gut-on-a-chip to model inflammatory processes

Abstract: Inflammatory bowel disease (IBD) is a complex multi-factorial disease for which physiologically relevant in vitro models are lacking. Existing models are often a compromise between biological relevance and scalability. Here, we integrated intestinal epithelial cells (IEC) derived from human intestinal organoids with monocyte-derived macrophages, in a gut-on-a-chip platform to model the human intestine and key aspects of IBD. The microfluidic culture of IEC lead to an increased polarization and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 69 publications
(108 reference statements)
1
83
0
Order By: Relevance
“…A significant need in this regard, and what poses an important limitation to our knowledge, is the challenge of obtaining direct access to relevant tissues such as the intestine and the enthesis structures. Use of newer in vitro systems like organ-on-a-chip and intestinal organoids derived from human subjects has the potential to allow mechanistic studies including microbe-host interactions [92][93][94][95] without having to use murine models.…”
Section: Spondyloarthritis Spondyloarthritis Spondyloarthritismentioning
confidence: 99%
“…A significant need in this regard, and what poses an important limitation to our knowledge, is the challenge of obtaining direct access to relevant tissues such as the intestine and the enthesis structures. Use of newer in vitro systems like organ-on-a-chip and intestinal organoids derived from human subjects has the potential to allow mechanistic studies including microbe-host interactions [92][93][94][95] without having to use murine models.…”
Section: Spondyloarthritis Spondyloarthritis Spondyloarthritismentioning
confidence: 99%
“…Other groups have successfully co-cultured 3-D gastrointestinal organoids with intraepithelial lymphocytes ( Nozaki et al, 2016 ), T cells ( Dijkstra et al, 2018 ), and both DCs and cytotoxic T cells ( Chakrabarti et al, 2018 ). Sophisticated microphysiological systems (MPSs) that integrate gastrointestinal epithelial cell monolayers and immune components also have been established by multiple groups ( Kim and Ingber, 2013 ; Kim et al, 2016 ; Shin and Kim, 2018 ; Beaurivage et al, 2020 ). However, monolayer systems frequently lack critical features of 3-D spherical organoids, such as oxygen gradients, crypt and gland formation and physiological tissue patterning ( Williamson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a pIOAC incorporating intestinal epithelial cells derived from human intestinal organoids and monocyte-derived macrophages has been successfully fabricated to simulate key aspects of the intestine of individuals with IBD. Intriguingly, the inflammatory trigger-induced gene expression profile in this model was similar to those in patients with IBD, opening the doors to personalized medicine [ 152 ]. Recently, studies with human intestinal organoids have shown that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) preferentially infects mature enterocytes over enteroendocrine and goblet cells [ 153 ].…”
Section: Future Perspectives In Personalized Medicinementioning
confidence: 99%